SISTEM PENGONTROLAN PH PADA IKAN HIAS AIR LAUT DENGAN METODE FUZZY LOGIC MAMDANI - Ramadhan Setya Novianto; Tri Nurwati; Eka Maulana (Jurnal Mahasiswa TEUB, 2022)
Water quality is the main parameter in the cultivation of freshwater ornamental fish and marine ornamental fish. To get healthy ornamental fish, water conditions must be maintained, one of which is the pH of the water. Generally fish need a water pH in the range of 6.5 to 8.5, which is considered the optimal range for good fish growth. Changes in the pH of seawater can adversely affect the life of marine biota, either directly or indirectly. Controlling the pH of water in marine ornamental fish using the Mamdani fuzzy logic method, by determining its membership function so that it can control the speed of pumping acid or alkaline solutions. From the results of the study, the tool can control the pH of seawater according to the setpoint membership function that has been set, namely 6.5-8.5 for 368-478 seconds by adjusting the pump output discharge according to the difference between the pH of the aquarium and the desired value.Keywords: pH, Fuzzy Logic Mamdani, Membeship Function